Adjunctive corticosteroid therapy and clinical recovery in hospitalized community-acquired pneumonia patients: a retrospective comparative study - Rostalina, Irma; Meiliana, Made Laksmi; Kusniawati, Mega Ayu (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Dysregulated inflammation in community-acquired pneumonia (CAP) has prompted investigation of corticosteroids as adjunctive therapy; however, their clinical utility remains contested, particularly in non-severe presentations and resource-limited settings. This study aims to evaluate the effect of adjunctive corticosteroid therapy on length of hospital stay and key clinical parameters in adult CAP patients at a secondary referral hospital in Bandar Lampung, Indonesia. This retrospective comparative study analyzed medical records of 59 eligible CAP patients admitted during 2023. Patients were categorized into steroid (n = 39) and non-steroid (n = 20) groups. Time to clinical improvement in temperature, cough, dyspnea, and respiratory rate, as well as length of hospital stay, were compared using chi-square and Fisher's exact tests. Steroid-treated patients had significantly longer hospital stays (28.2% vs. 5.0% with stays ≥5 days; p = 0.044), slower dyspnea resolution (p = 0.022), and delayed respiratory rate normalization (p = 0.042). No significant differences were observed for temperature (p = 0.653) or cough resolution (p = 0.679). Adjunctive corticosteroid therapy was not associated with clinical benefit in this cohort and was associated with prolonged hospitalization. Severity-based patient selection and standardized protocols are essential before routine corticosteroid use can be recommended in similar settings.